Deradicalisation of terrorists : a psychological perspective. - Shi, Priscilla Wanting. (2013)
Much of the previous theoretical discussions pertaining to the deradicalisation of extremists and terrorists have been discussed from political science and sociological perspectives (e.g. Mullins, 2010; QIASS, 2010). However psychological research has much to contribute in this area. This paper attempts to provide a better understanding of this process from a psychosocial perspective. The main research questions in this paper were: What are the concepts of deradicalisation? What is the underlying psychology of terrorism (radicalisation, involvement and deradicalisation)? How relevant are the existing deradicalisation and rehabilitation programs (DRPs) to the dynamics of radicalisation? What are the potential areas of improvement in DRPs?